2014
DOI: 10.1371/journal.pone.0109629
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Impact of Chromosomal Microarray on Paediatric Care in Hong Kong

Abstract: ObjectiveTo evaluate the clinical impact of chromosomal microarray (CMA) on the management of paediatric patients in Hong Kong.MethodsWe performed NimbleGen 135k oligonucleotide array on 327 children with intellectual disability (ID)/developmental delay (DD), autism spectrum disorders (ASD), and/or multiple congenital anomalies (MCAs) in a university-affiliated paediatric unit from January 2011 to May 2013. The medical records of patients were reviewed in September 2013, focusing on the pathogenic/likely patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 42 publications
2
34
0
Order By: Relevance
“…CMA yields significant rates of pathogenic or potentially pathogenic (VOUS) results [2,11,12,13,14,15,16,17,18,19,20], which have clinical utility for the case-by-case clinical management of individuals with these individually rare disorders [23,24,25,26,27,28,29,30,31,32,33,34]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CMA yields significant rates of pathogenic or potentially pathogenic (VOUS) results [2,11,12,13,14,15,16,17,18,19,20], which have clinical utility for the case-by-case clinical management of individuals with these individually rare disorders [23,24,25,26,27,28,29,30,31,32,33,34]. …”
Section: Discussionmentioning
confidence: 99%
“…Collectively this trend has resulted in corresponding increases in the clinical value of CMA testing [11,12,13,14,15,16,17,18,19,20,21,24,25,26,27,28,29,30,31,32,33,34]. In addition to guidelines on the clinical indications for CMA, the American College of Medical Genetics and Genomics (ACMG) has issued guidance on the appropriate content and design of such arrays and specifically opined that, “It is desirable to have enrichment of probes targeting dosage-sensitive genes known to result in phenotypes consistent with common indications for a genomic screen (e.g., intellectual disability, developmental delays, autism, and congenital anomalies)” [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of children receiving a change in clinical management by WGS results was 0.27 (95% Cl 0.17-0.40, I 2 =54%, four studies of 136 children), compared with 0.18 (95% Cl 0.13-0.24, I 2 -77%,twelve studies of 992 children) by WES, and 0.06 (95% Cl 0.05-0.07, I 2 =42%, eight studies of 4,271 children) by CMA (Figure 5). Meta-analysis of WGS and CMA groups, for which heterogeneity was not significant ( P =.09 and P =.10, respectively), demonstrated that the rate of clinical utility of WGS was higher than CMA ( P <.0001) 25,32,34,35,37,45,59-61 . Meta-analysis of four studies that reported comparisons of rates of clinical utility by WGS/WES and CMA within cohorts 25,32,37,45 .…”
Section: Resultsmentioning
confidence: 93%
“…The diagnostic yield of our cohort in Hong Kong is 3.5% but direct comparison is difficult as our study is the only one among the three that uses a clinical aCGH platform and reports only pathogenic/likely pathogenic CNVs using stringent clinical laboratory criteria [13]. We did not identify many known ASD-associated CNVs, perhaps due to the limited sample size of the cohort.…”
Section: Discussionmentioning
confidence: 99%